ALICE: A non-LTE plasma atomic physics, kinetics and lineshape code - Hill,EG; Perez-Callejo,G; Rose,SJ (High Energy Density Physics, 2018)
All three parts of an atomic physics, atomic kinetics and lineshape code, ALICE, are described. Examples of the code being used to model the emissivity and opacity of plasmas are discussed and interesting features of the code which build on the existing corpus of models are shown throughout.